2015
DOI: 10.1007/s00520-015-2639-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functional capacity in colorectal cancer patients

Abstract: Performance status was found to be the only significant predictor of functional capacity in this study. Assessing performance status may have an essential role in order to predict functional capacity in CRC patients. Future studies that include a larger sample size would more clearly elucidate the predictors and relationships of functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…[23][24][25] Most patients in our study had metastases, mainly locoregional, which is similar to findings by Montazeri et al 25 that patients with advanced cancer may have poorer QoL. 7,8,13 Zimmerman et al 26 also confirmed performance status to be an important determinant of QoL in advanced cancer.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…[23][24][25] Most patients in our study had metastases, mainly locoregional, which is similar to findings by Montazeri et al 25 that patients with advanced cancer may have poorer QoL. 7,8,13 Zimmerman et al 26 also confirmed performance status to be an important determinant of QoL in advanced cancer.…”
Section: Discussionsupporting
confidence: 79%
“…The third, the Symptom Scale, consists of three domains (pain, fatigue, nausea and vomiting) and six single items (dyspnea, sleep disorders, loss of appetite, constipation, diarrhea, and financial difficulties). 13,21 Questions 01-28 contained in the instrument are arranged in a four-point Likert scale, where the respondents classified each item with responses ranging from strongly disagree (1 point) to strongly agree (4 points). Questions 29 and 30, in turn, also used the Likert scale, but with answers ranging from 1 to 7 points, classified as unsatisfactory to satisfactory, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy adult subjects (40–80 years of age) the mean 6MWT distance was 571 ± 90 m with older subjects walking shorter distances than younger 7 . Additionally, the 6MWT has been established as an independent and convenient prognostic factor of surgically treated non‐small‐cell lung cancer 3,6,8,9 …”
Section: Introductionmentioning
confidence: 99%
“…CRF is influenced by the side effects of chemotherapy and radiation therapy 7,8) , physical function, the mental state 9) , nutrition, inflammation, and anemia [10][11][12] . In physical function, exercise tolerance and CRF are related 13) , and aerobic exercise is said to be beneficial for CRF 14) . It has been reported that CRF is associated with anxiety and depression in the psychological aspect 15) .…”
mentioning
confidence: 99%